2022
DOI: 10.15252/embr.202154195
|View full text |Cite
|
Sign up to set email alerts
|

LRH‐1/NR5A2 interacts with the glucocorticoid receptor to regulate glucocorticoid resistance

Abstract: Nuclear receptors are transcription factors with important functions in a variety of physiological and pathological processes. Targeting glucocorticoid receptor (GR) activity using glucocorticoids is a cornerstone in the treatment of patients with T cell acute lymphoblastic leukemia (T‐ALL), and resistance to GC‐induced cell death is associated with poor outcome and a high risk for relapse. Next to ligand‐binding, heterodimerization with other transcription factors presents an important mechanism for the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…By comparing the structure of the NR5A gene in different organisms, it was found that the structure of the NR5A2 gene in various organisms is conserved, and there is obvious gene duplication in the evolutionary process, indicating that the NR5A2 gene is not prone to mutations and has high specificity in the expression of lung CSCs [ 56 ]. Furthermore, the variable shear location of the mutation site is associated with survival prognosis and the degree of drug resistance in patients with LUAD, which will be conducive to the drug guidance of second-line therapy and locating drug-resistant mutation gene sites, and will greatly improve the survival time of patients [ [57] , [58] , [59] , [60] , [61] ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the structure of the NR5A gene in different organisms, it was found that the structure of the NR5A2 gene in various organisms is conserved, and there is obvious gene duplication in the evolutionary process, indicating that the NR5A2 gene is not prone to mutations and has high specificity in the expression of lung CSCs [ 56 ]. Furthermore, the variable shear location of the mutation site is associated with survival prognosis and the degree of drug resistance in patients with LUAD, which will be conducive to the drug guidance of second-line therapy and locating drug-resistant mutation gene sites, and will greatly improve the survival time of patients [ [57] , [58] , [59] , [60] , [61] ].…”
Section: Discussionmentioning
confidence: 99%
“…NR5A2 expression is downregulated in metabolic syndrome [26]. Relevant literature reports that NR5A2 interacts with glucocorticoid receptors to regulate glucocorticoid resistance [23,27]. Therefore, NR5A2 might affect metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…GCs, hormones synthesized by the adrenal glands, are released into the bloodstream to maintain homeostasis and regulate the body's response to various stressors [ 95 , 96 ]. These hormones exert their effects through interaction with the GC receptor (GR), which is ubiquitously expressed across various cell types, thereby influencing a broad spectrum of pathophysiological pathways with pronounced impacts on metabolism and immunity [ 97 ]. The suppressive effect of GCs on T cell functionality is well established [ 98 , 99 ].…”
Section: Gc Production By Tumor Cells and Its Role In Immunosuppressionmentioning
confidence: 99%